SURVEI KEBERADAAN VIRUS WHITE SPOT SYNDROME (WSS) PADA CACING POLYCHAETA DI TAMBAK UDANG: STUDI KASUS DI KENDAL - A H Desrina; Condro Haditomo; S B Prayitno (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
White Spot Syndrome (WSS) disease, caused by White Spot Syndrome Virus (WSSV), is an important shrimp disease in Kendal, one of many shrimp production area in Central Java Province. It has been indicated that polychaetes may be one of many vectors of WSSV. The objective of this research is to determine the occurrence and prevalence of WSSV infection in polychaetes obtained from shrimp pond with various culture condition. Pond A (semi intensive, monoculture P. Vannamei, pond size 2000 m2; 2); Pond B (extensive, monoculture P. Vannamei, pond size 5000 m2) and C (extensive, polyculture P. vannamei and tilapia Tilapia nilotica pond size 6000 m2). Sediment was obtained with PVC and sieved through a series of sieve shaker. Polychaetes found were counted and identified. Polychaetes was tested for WSSV infection with 1-step nested PCR and prevalence of infection was calculated. Polychaetes found consisted of 2 species namely Dendronereis sp and Nereis sp Polychaetes density (individu/ m2 ) for pond A, B and C are 102,1168 and 207 respectively. Prevalence of WSSV infection in Polychaetes from individual ponds is 29,4 % (A); 20% (B); and 12, 94 % (C). This prevalence is considered low compare to other similar research.